Seven Paradoxes of Business Process Management in a Hyper-Connected World - Daniel Beverungen; Joos C. A. M. Buijs; Jörg Becker; Claudio Di Ciccio; Wil M. P. van der Aalst; Christian Bartelheimer; Jan vom Brocke; Marco Comuzzi; Karsten Kraume; Henrik Leopold; Martin Matzner; Jan Mendling; et al. (Business & Information Systems Engineering, 2020)
Business Process Management is a boundary-spanning discipline that aligns operational capabilities and technology to design and manage business processes. The Digital Transformation has enabled human actors, information systems, and smart products to interact with each other via multiple digital channels. The emergence of this hyper-connected world greatly leverages the prospects of business processes – but also boosts their complexity to a new level. We need to discuss how the BPM discipline can find new ways for identifying, analyzing, designing, implementing, executing, and monitoring business processes. In this research note, selected transformative trends are explored and their impact on current theories and IT artifacts in the BPM discipline is discussed to stimulate transformative thinking and prospective research in this field.
Keywords: 000; Business process management (BPM); Social computing; Smart devices; Big data analytics; Real-time computing; BPM life-cycle